Relationship between information access, service quality, costs saving, cultural similarity and supporting service towards medical (dental) tourism patients’ satisfaction - Fuad H. Akbar; Fridawaty Rivai; Andi Z. Abdullah; Abdul H. Awang (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine the relationship between information access, service quality, cost savings, cultural similarities and supporting service systems towards dental tourism patient’s satisfaction at Hospital X.Material and Method: This study was an observational analytic study with a cross sectional approach. The analysis used in this study was performed using SPSS version 23 and correlation analysis.Results: Service quality had a risk of 3.36 times affecting the level of satisfaction and access to information had a risk of 3.64 times affecting the level of satisfaction, and showed a statistically significant relationship (p <0.05).Conclusion: Research shows a statistically significant relationship between service quality and access to information on the level of patient satisfaction.